2020
DOI: 10.1097/jcma.0000000000000319
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal and liver manifestations in patients with COVID-19

Abstract: As the outbreak of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has rapidly spread over the world, the World Health Organization has declared the outbreak of COVID-19 an international public health emergency. Besides typical respiratory symptoms and signs of COVID-19, digestive symptoms and liver injury have been frequently reported during the course of the disease. In this review, we summarized the recent studies reporting of gastrointestinal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
162
0
30

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(211 citation statements)
references
References 32 publications
7
162
0
30
Order By: Relevance
“…In the present study, bloating was reported as one of the gastrointestinal symptoms which was in line with the ndings of Pan et al who reported the most common gastrointestinal symptoms as anorexia, diarrhea, vomiting, and abdominal pain, respectively (41). Also, patients with concomitant gastrointestinal ndings along with other symptoms may experience a more severe form of the disease increasing the risk of mortality (37,41). Therefore, clinical specialists should be vigilant about gastrointestinal symptoms such as diarrhea and anorexia, even in the absence of respiratory manifestations, as important symptoms of Covid-19 disease.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, bloating was reported as one of the gastrointestinal symptoms which was in line with the ndings of Pan et al who reported the most common gastrointestinal symptoms as anorexia, diarrhea, vomiting, and abdominal pain, respectively (41). Also, patients with concomitant gastrointestinal ndings along with other symptoms may experience a more severe form of the disease increasing the risk of mortality (37,41). Therefore, clinical specialists should be vigilant about gastrointestinal symptoms such as diarrhea and anorexia, even in the absence of respiratory manifestations, as important symptoms of Covid-19 disease.…”
Section: Discussionsupporting
confidence: 90%
“…with pneumonia, (1,8) SARS-CoV-2 has been associated with multiple extrapulmonary effects, (1) including gastrointestinal and hepatic manifestations. (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Previous studies have identified increased liver tests in 14%-78% of affected persons, primarily serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT). (16)(17)(18) Although the prevalence and severity of abnormal liver tests have been described, (19) their relationship to baseline liver tests preceding COVID-19 hospitalization remains poorly understood.…”
mentioning
confidence: 99%
“…The other indicators concurrent with the progress of the disease were the increases of both CRP and ESR. The wife showed elevated bilirubin, which also occurred after taking iopinavir/ritonavir, and it has been reported that the administration of iopinavir/ritonavir is related to liver function damage 6 ,at the same time, the patient had obvious nausea and discomfort after taking iopinavir/ritonavir which gradually disappeared after the drug was discontinued, so the elevated bilirubin was likely to be associated with both iopinavir/ritonavir medication and viral infection which have been reported 18 .…”
Section: Discussionmentioning
confidence: 84%